Kesenjangan Implementasi Dalam Penatausahaan Barang Milik Negara Yang Berasal Dari Kontraktor Kontrak Kerjasama - Cahyaningrum, Cahyaningrum; Halim, Abdul (JURNAL RISET MANAJEMEN SEKOLAH TINGGI ILMU EKONOMI WIDYA WIWAHA PROGRAM MAGISTER MANAJEMEN, 2015)
Oil and gas industry began in the Dutch colonial era. Based on Article 78 Government Regulation No. 35 Year 2004 on Upstream Oil and Gas, that all goods and equipment which directly used in the Upstream Oil and Gas Activity that purchased by Contractor becomes to State assets which is developed by the government and managed by SKK Migas. Enactment of Government Regulation No. 6 of 2006 about the management of State assets / Regional assets (BMN / BMD) as the implementation of the mandate of Law Number 17 Year 2003 on State Finance and Law No. 1 of 2004 on State Treasury is a new chapter for the management of state assets more orderly , accountable, and transparent. SKK Migas as an institution whose function is to supervise the implementation of the Production Sharing Contract (PSC) has purpose to provide maximum benefit for the country. On the other hand, state asset management by the Government aims to achieve accountability through the orderly administration and better management of State assets. The difference between that purpose, can lead to implementation gaps. This research was conducted with the aim of knowing the activity of administration of State assets originating from Contractor of Cooperation Contract which has the highest implementation gaps, find the source of the cause and finding the impact on the administration of State assets originating from Contractor of Cooperation Contract. Measurements implementation gaps using tools that called integrity scorecard. Integrity scores obtained by submitting some questionnaires to the respondents. The respondents in this study is the contractors which have commercial production. The research results illustrate the reporting activity has the highest implementation gap. It can also be seen from the BPK findings on Internal Control System in State assets administration originating from Contractor of Cooperation Contract on LKPP Year 2007 - 2013. Based on the descriptive analysis of the State assets which originating from Contractor of Cooperation Contract enforcement background and administration activity analysis, it can be concluded that the cause of the implementation gap is the political pressures, bureaucratic overlap, and resource constraints in the implementation of the regulation.Based on the inductive analysis of the weakness symptoms that occur in the administration of State assets originating from Contractor of Cooperation Contract, can be concluded that the data presented in the central goverment financial report (LKPP) potentially not comply with the qualitative characteristics standards such us relevant, reliable, comparable and understandable.Keywords: Implementation Gaps, Administration, State assets which originating from Contractor of Cooperation Contract.